Agency, communion, and pubertal status: Separating between‐ and within‐person associations to examine social goals development. Issue 5 (22nd April 2021) - Meisel, Samuel N.; Paul, Matthew J.; Colder, Craig R.
Abstract: Objectives: Agentic (status/independence) and communal (acceptance/connectedness) social goals are thought to shape how adolescents transact with their social environments. Despite their theoretical importance, little work has focused on the development of these higher order personality dimensions. Informed by developmental neuroscience and evolutionary psychology theoretical frameworks, the current study examined associations between pubertal status, a person's level of pubertal development at a single point in time, and agentic and communal social goals across early to middle adolescence. Methods: This longitudinal study consisted of 387 (55% female) adolescents (Wave 1 M age = 12.1) who were assessed annually across three waves. Hierarchical linear modeling was used to examine growth in pubertal status and agentic and communal goals and to distinguish between‐ and within‐person associations between pubertal status and social goals. Results: Within‐person pubertal status was concurrently associated with higher levels of agentic and communal goals. In the cross‐sectional and longitudinal models, between‐person pubertal status was associated with higher levels of agentic social goals. No support was found for social goals prospectively predicting pubertal status. Conclusions: These findings provide support for the hypothesis that puberty, in part, may drive developmental shifts in the value adolescents place on close peer relationships and obtaining status and independence.